Pengembangan LKS PAI Berbasis Kecerdasan Buatan (AI) Untuk Meningkatkan Pemahaman Siswa Kelas X SMK Turen-Malang - Abi Walid; Evi Nurhalimah (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This research is motivated by the rapid development of digital technology that has not been optimally integrated into Islamic Religious Education (PAI) learning tools in vocational schools. Conventional Student Worksheets (LKS) tend to be statistical in nature so they are less able to facilitate the independent learning needs of generation Z students. The purpose of this research is to develop, test the knowledge of the feasibility, and effectiveness of Artificial Intelligence (AI)-based LKS in improving the conceptual understanding of class X students at SMK Turen-Malang. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved material experts, media experts, and class X students of SMK Turen. Data were collected through questionnaire validation, observation, and learning outcome tests (pre-test and post-test). The results of the study show that: (1) AI-based LKS were declared “Very Feasible” by material experts (92%) and media experts (88%); (2) Implementation of AI features such as adaptive feedback and intelligent tutors significantly makes it easier for students to understand complex material; (3) There was an increase in student understanding as evidenced by an N-Gain score of 0.72, which falls into the "High" category. The conclusion of this study is that AI-based LKS are effective and suitable for use as an innovative medium for Islamic Religious Education learning in the digital era.